Development of the Mathematical Model of the Platforming Block of the Catalytic Reforming Unit - Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2022)
Many branches of the national economy, including oil and petrochemical, consist of complex combinations of technological installations. An optimal control of technological processes occurring in each of these complex units, in turn, is an urgent issue. The high requirements for the quantity and quality of petroleum products in the modern period necessitate the use of complex structured technological systems. The effective management of complex structural technological systems depends on the physical formalization of issues of optimal control of technological processes of various classes, the correct construction of optimal control algorithms based on mathematical models. Given the above, in the presented research work was studied to develop and verify the adequacy of the mathematical model of the block reforming technological complex catalytic reforming on the basis of data collected during the experiment. In developing the mathematical model, various regimes calculated by the composition of raw materials were taken into account.